Connecting Adolescents'Voice through Social Media and the Implication on Government Policy Making - Kusumasari Bevaola, Bevaola (2012)
Citizen participation is simply understood as taking part in government decision-making process. The development of social networking affords a new way forthe youth to engage in policy formulation.This study highlights the way teenagers can use social media to legitimately participate in politics. The Survey comprised 120 teenagers drawn fromthe 13-19agegroup in Yogyakarta, Indonesia. The survey entailed observation of teenagers' status on Facebook and Twitter.Study findings show that there has been a shift in the way teenagers participates in politics. Social networking has become major influence in teenagers' participation in politics owing to its due its practicality, flexibility and ability to enable them express their political and social concerns in personal ways. This findings highlights the importance of social networking as space which the government can use to engage teenagers' voice into policy formulation. This article, examines contextual issues teenagers encounter in their ' lives, coupled with review of literature review on adolescents participation in politics, to determine whether social media is an effective policy-making tool in communitypolitical participation